Languaging their Way from Media to Market: The Role of Specialized Language in Influencing and Persuading Consumers (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present research paper is an attempt to explore how far the language goes in carrying adesired message prepared by professionalscopywriters in order to sell productsservices to the potentialbuyers at the other end. The language experts resort to highly specialized language in order to influenceand persuade people into buying the stuff being promoted making effective use of language over themedia and getting the desired outcome at the market. But language is not a small term there are severallevels - graphology, phonology, lexisvocabulary, syntaxsentence structure, and semanticsmeaning.Each of these levels are further divided into sub-levels which are diligently worked upon for success.